Metaphysics as a science in classical German philosophy
1 online resource (ix, 370 pages)
Keywords: "This volume is dedicated to questions about the nature and method of metaphysics in Classical German Philosophy. Its chapters offer original investigations into the metaphysical projects of many of the major figures in German philosophy between Wolff and Hegel. The period of Classical German Philosophy was an extraordinarily rich one in the history of philosophy, especially for metaphysics. It includes some of the highest achievements of early modern rationalism, Kant's critical revolution, and the various significant works of German Idealism that followed in Kant's wake. The contributions to this volume critically examine certain common themes among metaphysical projects across this period, for example, the demand that metaphysics amount to a science, that it be presented in the form of a system, or that it should proceed by means of demonstration from certain key first principles. This volume also includes material on influential criticisms of metaphysical projects of this kind. Metaphysics as a Science in Classical German Philosophy is a useful resource for contemporary metaphysicians and historians of philosophy interested in engaging with the history of the methodology and epistemology of metaphysics"--